2018
DOI: 10.3892/ol.2018.8502
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the anticancer effects of vitamin K2 (Review)

Abstract: Despite the availability of multiple therapeutic methods for patients with cancer, the long-term prognosis is not satisfactory in a number of different cancer types. Vitamin K2 (VK2), which exerts anticancer effects on a number of cancer cell lines, is considered to be a prospective novel agent for the treatment of cancer. The present review aims to summarize the results of studies in which VK2 was administered either to patients with cancer or animals inoculated with cancerous cells, particularly investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 52 publications
0
52
0
1
Order By: Relevance
“…The authors emphasized that a combination treatment of vitamin K2 and chemotherapeutics could lead to better results with fewer side effects. However, much more data are necessary to draw final conclusions [ 175 ]. Zhong et al (2012) concluded that vitamin K2 significantly improved one-year overall survival in patients with liver cancer [ 176 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors emphasized that a combination treatment of vitamin K2 and chemotherapeutics could lead to better results with fewer side effects. However, much more data are necessary to draw final conclusions [ 175 ]. Zhong et al (2012) concluded that vitamin K2 significantly improved one-year overall survival in patients with liver cancer [ 176 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because there are limited studies concerning vitamin K in UFs, we explored some of the possible mechanisms using cancer models that considered its anti-inflammatory, antioxidative, and anti-carcinogenic properties [174]. Xv et al (2018) concluded that vitamin K2 could positively inhibit the growth of cancer cells. The authors emphasized that a combination treatment of vitamin K2 and chemotherapeutics could lead to better results with fewer side effects.…”
Section: Vitamin K and Uterine Fibroidsmentioning
confidence: 99%
“…A currently active field of research around vitamin K relates to its potential anti-cancer effect. Although this topic will not be explored in this review, vitamin K has been implicated with the inhibition of several neoplastic cell lines mainly by inducing apoptosis and cell cycle arrest of cancer cells through various mechanisms [101]. Among the different forms of vitamin K tested, vitamin K2 was shown to inhibit several cancer cell lines without side effects and has been selected as a promising agent for cancer prevention and clinical therapy.…”
Section: Vitamin K Functionsmentioning
confidence: 99%
“…Vitamin K2 (menaquinone) induces apoptosis [48]. Studies of brain, stomach and colon cancer cell lines have shown that vitamin K2 inhibits the cell cycle.…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%
“…Laboratory experiments and epidemiological research have demonstrated that vitamin K2 has immense potential for treating various types of cancer. Vitamin K2 inhibits the initiation, promotion and progression of human hepatocellular carcinoma cells [48]. In various types of lung cancer, including small-cell carcinoma, squamouscell carcinoma and adenocarcinoma, vitamin K2 induces apoptosis by activating 'suicide' proteins [53].…”
Section: Annals Of Agricultural and Environmental Medicinementioning
confidence: 99%